The Fiesta and the Cerro. Rocksi Broadcasting on Social Media From Xaamkëjxp - Elena Nava Morales (Changing Societies & Personalities)
This work presents the case of a young woman Rocksi, who works with social media and has a strong influence in her region. She lives in Xaamkëjxp, Oaxaca, in the southwest state of Mexico. Her work shows us both the religious customs and the politics of the communities through live transmissions on her Facebook and YouTube profiles. In 2024, she transmitted several celebrations in Xaamkëjxp related to religious celebrations as she was invited to help a family that had a comisionados de festejo cargo. Rocksi filmed various activities illustrating the importance of ethnic religious practices in the community and the strength and vitality of the religious and political cargos. In the text, I will delve deeper into the topic through ethnographic description.